Mercury and selenium intake by seafood from the Ionian Sea: A risk evaluation - Copat, Chiara; Vinceti, Marco; D'Agati, Maria Grazia; Arena, Giovanni; Mauceri, Valeria; Grasso, Alfina; Fallico, Roberto; Sciacca, Salvatore; Ferrante, Margherita (Ecotoxicology and environmental safety, 2014)
The subject of the present study is the evaluation of the concentrations of mercury (Hg) and selenium (Se) in fish and shellfish from the Gulf of Catania (Ionian Sea) and the assessment of related risk-based consumption limits per single contaminant in adults and children. In contrast to the potential harm from Hg, Se is an essential element that is normally found in high levels in seafood. If the amount of Hg is high enough, it could bind Se and irreversibly inhibit selenium-dependent enzymes. Thus, adequate levels of Se need to be available to replace the amount of Se lost to Hg sequestration, thereby maintaining normal selenoprotein synthesis. Hg analysis was conducted using a flow injection analysis system coupled with an atomic adsorption spectrometer, and Se analysis was conducted using an inductively coupled plasma mass spectrometry (ICP-MS). Of the trace elements investigated, only Hg has a limit set by the European Community for human consumption, and this was never exceeded. Nevertheless, based on Target Hazard Quotient (THQ) over 1, and on the Estimated Daily Intake per meal (EDIm) higher than the Provisional Tolerable Intake (PTI) suggested by the Joint FAO/WHO Expert Committee on Food Additive (JECFA), Hg oral exposure derived from consumption of the benthonic fish and of the bigger pelagic fish species analyzed, could follow the occurrence of systemic effects. Se was found always in molar excess respect to Hg in all pelagic fish and in the shellfish, nearly equimolar in the benthonic fish. Determining the evidence that foods, such as pelagic fish, with high molar excess of Se, could contribute to replace the amount of Se bound to Hg and thereby maintaining normal selenoprotein synthesis, is useful for a better understanding of the seafood safety. •Advisories concerning consumption rates to minimize risks to human health have been documented.•Hg target hazard quotient suggests that humans should minimize meals/week of certain fish species.•Surely, consuming pelagic fish of small size could balance benefits and risks.•A significant molar excess of Se with respect to Hg was found in pelagic and shellfish species.•A diet rich in Se could contribute to maintain antioxidant capability and also, promote Hg excretion.